Community Service in Strenghthening the Branding of Gadung Chips MSME Actors in Dander Bojonegoro District - Reza Anggapratama; Dwi Irnawati; Sova Selviana; Esti Nur Fadila; Syifa’un Niswah (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Mbah Kung's gadung chips MSMEs actually face many problems, including low utilization of advanced innovation. There is no information regarding the use of brand branding in introducing goods to buyers. Gadung chips MSME actor Mbah Kung is still focused on exchanging goods but has not carried out brand branding properly. Unawareness and lack of information, exaggerated self-image and fear, as well as the perpetrator's affinity for innovative thoughts and immediate feelings of pleasure with the approach of the completed exchange. As a lecturer, I help provide solutions by involving students in community service activities, which include socialization and training on branding strategies for Mbah Kung gadung chips MSME products to support business stability and expand market reach. The service method is carried out directly at Mbah Kung's Gadung chips MSME location. The results of the community service showed that Mbah Kung's Gadung chips MSMEs were happy with the material introduced. Expanding attention to the importance of using product marking as a guide to the goods being made as well as preparation for making brand branding with Canva by practicing directly and expanding the ability to create attractive brand branding as desired to make consumers loyal to the products created.